The association between sugars sweetened beverages and glycemic profile among children and youth: A systematic review and dose-response meta-analysis - Mahdieh Abbasalizad Farhangi; Zeinab Nikniaz; Seyedeh-Tarlan Mirzohreh; Leila Nikniaz (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2025)
Background: This study aimed to assess the effects of Sugar-Sweetened Beverages (SSBs) consumption on fasting serum insulin (FSI), fasting plasma glucose (FPG), and HOMA-IR levels among children. Methods: Databases including PubMed/MEDLINE, Scopus, EMBASE, Cochrane Library, and Web of Science were searched up to March 2025. Observational studies reporting the connection of SSBs consumption with FPG, FSI, and HOMA-IR levels were included. STATA version 15 was used to analyze the data. Results: 11 studies with 22,713 subjects were included in this meta-analysis. Greater intake of SSBs was not significantly linked to higher fasting plasma glucose (WMD: 0.01; CI -0.04 –0.07; P = 0.63) and fasting serum insulin levels (WMD: 0.54; 95 % CI, −0.4, 1.49; P = 0.26). However, high SSBs consumption was significantly associated with a 0.21 increase in HOMA-IR in adolescents and children (WMD: 0.21; CI, 0.03–0.37; P = 0.02). In dose-response meta-analysis, no departure from linearity was detected between SSBs intake and changes in FPG, FSI, and HOMA-IR levels. Conclusions: High SSBs intake was linked to increased HOMA-IR levels among adolescents and children. Further extensive prospective long-term interventions are suggested to confirm the detected associations.